Desain Pembelajaran Segi Empat dengan Pendekatan RME Pada Siswa SMP - Risa Yuniarti (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
The importance of STEM education has been recognized for preparing diverse students to cultivate future job opportunities in STEM, and for a nation as a whole for technological innovation and national prosperity and security (Li, Schoenfeld, Disessa. 2019). The STEM approach requires the right learning model to be able to achieve learning objectives. One of the learning models that can be used with STEM is PjBL (Project Based Learning). Project-Based Learning (PjBL) is a learning model that teaches concepts in the curriculum through a student-centered project so that they can work autonomously, collaboratively and through assignments. STEM (Science, Technology, Engineering and Mathematics) is learning that integrates the concepts of science, technology, engineering and mathematics. Students are able to apply STEM knowledge practically and produce meaningful learning through PjBL activities. Combining PjBL with STEM has an influence on students' attitudes towards future career pursuits (Tseng, Chang, Lou, Chen. 2013).